Operative Treatment of Syndesmotic Injuries With Assisted Arthroscopic Reduction. Issue 4 (December 2018) - Cabe, Taylor N.; Rodriguez, Kaitlyn A.; Drakos, Mark C.
Abstract : There continues to be a lack of consensus on the proper treatment of syndesmotic injuries in the literature. Currently, much of the operative debate lies between using a suture-button technique or transsyndesmotic screw fixation to treat the injury. There are further arguments surrounding screw fixation involving the size and number of the screws, the number of cortices, and whether or not the hardware is to be removed. For patients presenting with a syndesmotic injury, it is important to properly diagnose and address the type of injury in order to prevent long-term morbidity and ultimately, degenerative arthritis. In the case of unstable syndesmotic injuries, we advocate the use of screw fixation, using 2, fully threaded, 4.0-mm cortical screws through 4 cortices and removal of the hardware 3 months postoperatively. Level of Evidence: Level IV.